##
**PRODUCTS**

We get one expression when two or more expressions are multiplied. The result is universally true and then it is called an identity. These identities can be used to reduce large products into simpler ones. For example (x + a) is one expression and (x - a) is another expression and when they are multiplied we get x

^{2} - a

^{2}. (x + a)(x - a) = x

^{2} - a

^{2} is an identity. Let us look at some of the products.

*(x + a)(x + b) = x*^{2} + (a + b)x + ab

*(a + b)(a - b)= a*^{2} - b^{2}

*(a + b)*^{2} = a^{2} + 2ab + b^{2}

*(a - b)*^{2} = a^{2} - 2ab + b^{2}

*(a + b + c)*^{2} = a^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca

###
Product of two expressions (x + a) and (x + b)

*(x + a)(x + b) *
= x(x + b) + a(x + b)

= x

^{2} + bx + ax + ab

=

*x*^{2} + (a + b)x + ab
###
Product of sum and difference of two terms a and b

*(a + b)(a - b)*
= a

^{2} + ba - ba - b

^{2}
*= a*^{2} - b^{2}

###
Square of binomials

*(a + b)*^{2}
= (a + b)(a + b)

*= a*^{2} + 2ab + b^{2}
*(a - b)*^{2}
= (a - b)(a - b)

*= a*^{2} - 2ab + b^{2}

###
Square of trinomials

*(a + b + c)*^{2}
= (a + b + c)(a + b + c)

= (a(a + b + c) + b(a + b + c) + c(a + b + c))

= (a

^{2} + ab + ac + ba + b

^{2} + bc + ca + cb + c

^{2})

=

* a*^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca